Association Between FokI Polymorphism of Vitamin D Receptor Gene and Lumbar Spine Disc Degeneration: A Systematic Review and Meta-Analysis. (May 2021) - Castillo-Avila, Rosa Giannina; González-Castro, Thelma Beatriz; Tovilla-Zárate, Carlos Alfonso; Juárez-Rojop, Isela Esther; López-Narváez, María Lilia; Rodríguez-Pérez, José Manuel; Suárez-Méndez, Samuel
Abstract : Objective: The aim of the present meta-analysis was to explore the association between FokI polymorphism of the vitamin D receptor gene and lumbar spine disc degeneration. Design: The search was performed in PubMed, Scopus, and Web of Science databases up to January 2020. The authors selected nine studies comprising a total of 1549 cases and 1672 controls. The association analysis included the allelic, dominant, recessive, homozygous, and heterozygous genetic models. Odds ratios with 95% confidence intervals were used to evaluate the association. The Newcastle-Ottawa Scale was used to measure the quality of the studies included in the analyses; a cut-off of 6 stars was applied. Results: This meta-analysis indicated that FokI polymorphism is significantly associated with lumbar degenerative disc disorder and disc herniation in the homozygous (odds ratio, 1.77; 95% confidence interval, 1.23–2.54; Z test P = 0.002, Q test P = 0.416) and recessive (odds ratio, 1.53; 95% confidence interval, 1.23–1.90; Z test P < 0.000, Q test P = 0.224) models. Conclusions: This study indicates that the vitamin D receptor gene FokI polymorphism may be correlated with the risk of developing a lumbar degenerative disc disorder and disc herniation. However, the small sample population studied and the lack of an evaluation of environmental factors must be taken as limitations in the present meta-analysis. Abstract : Supplemental digital content is available in the text.